1993
DOI: 10.1007/bf00932245
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity and sporogony ofCaryospora-type oocysts ofIsospora rivolta obtained by heating

Abstract: The infectivity and sporogony of Caryospora-type oocysts of Isospora rivolta obtained by heat treatment were examined. Fresh unsporulated oocysts of I. rivolta were heated at 50 degrees C for 5 min, then poured into a cold 2% potassium dichromate solution and incubated at 25 degrees C. To observe the stage of sporulation, 100 oocysts were examined at 2-h intervals after incubation. The earliest sporulated oocysts were observed at 14 h and the sporulation time was 22 h, similar to that of nontreated oocysts. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…These oocysts remained viable and infectious to cats. 21 Although we did not determine the effect of heat induction on the generation of Caryosporalike oocysts in I. belli, spontaneous development of this stage occurred during a range of five days to two weeks at ambient temperature (25-30°C). If the viability period of I. belli in the environment after complete sporulation was limited, unsynchronized sporulation could extend the period of transmission of this important enteric coccidian protozoa.…”
Section: Discussionmentioning
confidence: 91%
“…These oocysts remained viable and infectious to cats. 21 Although we did not determine the effect of heat induction on the generation of Caryosporalike oocysts in I. belli, spontaneous development of this stage occurred during a range of five days to two weeks at ambient temperature (25-30°C). If the viability period of I. belli in the environment after complete sporulation was limited, unsynchronized sporulation could extend the period of transmission of this important enteric coccidian protozoa.…”
Section: Discussionmentioning
confidence: 91%
“…When the sporozoites are fully visible, the oocyst is considered to be sporulated. A small percentage (Ͻ2%) of oocysts are Caryospora-like and contain one sporocyst which encloses eight sporozoites (96,108,121,193) (Fig. 1b).…”
Section: Sporogonymentioning
confidence: 99%
“…1b). Heat treatment of unsporulated I. rivolta oocysts at 50ЊC for 5 min increased the numbers of Caryospora-like oocysts that were produced after sporulation (121). These Caryospora-like oocysts of I. rivolta were infectious for mice (paratenic hosts) and cats.…”
Section: Sporogonymentioning
confidence: 99%
“…Little is known about factors that induce the development of Caryospora-like oocysts of what would normally be Cystoisospora species oocysts. Matsui et al (1993) demonstrated that heat treatment of unsporulated Cystoisospora rivolta oocysts from cats at 50 C for 5 min caused an increase in the numbers of Caryospora-like oocysts that were produced after sporulation. Oocysts collected from cats inoculated with Caryospora-like oocysts of C. rivolta were Cystoisospora-like after sporulation, indicating that heat treatment did not induce a stable mutation.…”
mentioning
confidence: 99%
“…The biological importance of these Caryospora-like oocysts is unknown. The heat stress treatment method of Matsui et al (1993) may prove to be a useful method to examine gene expression associated with sporogony of C. canis oocysts.…”
mentioning
confidence: 99%